2014
DOI: 10.3855/jidc.4734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of class 1 and 2 integrons from clinical and environmental Salmonella isolates

Abstract: The presence of an integron did not necessarily confer resistance. Future studies will seek to identify the mechanism behind integron-mediated antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…All isolates were investigated for the presence of class 1, 2, and 3 integrase-encoding genes, through PCR amplification using primers reported elsewhere (Leverstein-Van Hall et al, 2002 ; Corrêa et al, 2014 ; Manageiro et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…All isolates were investigated for the presence of class 1, 2, and 3 integrase-encoding genes, through PCR amplification using primers reported elsewhere (Leverstein-Van Hall et al, 2002 ; Corrêa et al, 2014 ; Manageiro et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic discs (Oxoid, England) were used to determine the susceptibility of the strains to 15 antibiotics: minocyline (30 μg/disc), chloramphenicol (30 μg/disc), amikacin (30 μg/disc), ampicillin (10 μg/disc), gentamicin (120 μg/disc), teicoplanin (30 μg/disc), cefotaxime (30 μg/disc), cefoxitin (30 μg/disc), oxacillin (1 μg/disc), levofloxacin (5 μg/disc), aztreonam (30 μg/disc), penicillin (10 μg/disc), rifampicin (5 μg/disc), tetracycline (30 μg/disc), and vancomycin (30 μg/disc), analyses were done in duplicate. Each isolate was classified as resistant (R), sensitive (S) and/or intermediate (I) according to the inhibition zone diameters in agreement with the Clinical and Laboratory Standards Institute tables [51].…”
Section: Methodsmentioning
confidence: 99%
“…All integrons are usually composed of three key elements necessary for the capture of exogenous genes: an intI gene; a primary recombination site ( attI ); and an outward- orientated promoter (Pc) [ 163 ]. It has been found that class I integrons contribute to antimicrobial resistance in Salmonella isolates and Stenotrophomonas maltophilia , respectively [ 164 , 165 ]. A new rifampin resistance gene arr-2 , located on a gene cassette within a class I integron, was found in P. aeruginosa [ 166 ].…”
Section: The Third Line Of Defense: Intracellular Alterationmentioning
confidence: 99%